ISCAS'99. Proceedings of the 1999 IEEE International Symposium on Circuits and Systems VLSI (Cat. No.99CH36349)
DOI: 10.1109/iscas.1999.777579
|View full text |Cite
|
Sign up to set email alerts
|

Complex discriminative learning Bayesian neural equalizer

Abstract: Traditional approaches to channel equalization are based on the inversion of the global (linear or nonlinear) channel response. However, in digital links the complete channel inversion is neither required nor desirable. Since transmitted symbols belong to a discrete alphabet, symbol demodulation can be e ectively recasted as a classiÿcation problem in the space of received symbols. In this paper a novel neural network for digital equalization is introduced and described. The proposed approach is based on a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Supervised neural networks, such as MLP and RBF, motivated by their universal approximation property, have been successfully used as nonlinear tools for channel equalization [11]. It has been demonstrated that the performance of MLP-or RBF-based adaptive filters usually outperform traditional linear techniques in many common signal processing applications [12], [20], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Supervised neural networks, such as MLP and RBF, motivated by their universal approximation property, have been successfully used as nonlinear tools for channel equalization [11]. It has been demonstrated that the performance of MLP-or RBF-based adaptive filters usually outperform traditional linear techniques in many common signal processing applications [12], [20], [25].…”
Section: Introductionmentioning
confidence: 99%